The Impact of Whole Brain Global Functional Connectivity Density Following MECT in Major Depression: A Follow-Up Study - Li, Xiao; Meng, Huaqing; Fu, Yixiao; Du, Lian; Qiu, Haitang; Qiu, Tian; Chen, Qibin; Zhang, Zhiwei; Luo, Qinghua (Frontiers in Psychiatry, 2019)
To explore the impact of global functional connectivity density（gFCD） in depressive patients after modified electroconvulsive therapy (MECT) and analyze the relationship between gFCD and clinical outcome. Thirty-seven subjects were evaluated based on the depression diagnostic criteria in the international Classification of diseases 10 (ICD-10) which comprised of a depressive group (24 subjects finished the follow-ups) and a healthy control group with 13 normal subjects. All participants received Hamilton Depression Scale (HAMD) scores and resting-state functional magnetic resonance imaging scans. The gFCD significantly increased in the posterior-middle insula, the supramarginal gyrus, and the dorsal medial prefrontal cortex (dmPFC) before MECT treatment compared to healthy control subjects, and the gFCD statistically increased in the perigenual anterior cingulate cortex (pgACC), the orbitofrontal cortex bilaterally and the left-supramarginal gyrus after MECT, and it decreased significantly in the posterior insula. The gFCD in the pgACC and the right orbital frontal cortex of the depressive group before MECT showed a positive correlation with HAMD scores after treatment. According to the impact of gFCD in depressive patients after MECT, the aforementioned brain region may become an indicator of MECT effect.